2019
DOI: 10.5194/acp-19-11985-2019
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying aerosol size distributions and their temporal variability in the Southern Great Plains, USA

Abstract: Abstract. A quality-controlled, 5-year dataset of aerosol number size distributions (particles with diameters (Dp) from 7 nm through 14 µm) was developed using observations from a scanning mobility particle sizer, aerodynamic particle sizer, and a condensation particle counter at the Department of Energy's Southern Great Plains (SGP) site. This dataset was used for two purposes. First, typical characteristics of the aerosol size distribution (number, surface area, and volume) were calculated for the SGP site, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…Similar to previous studies at the SGP (Marinescu et al, 2019;Wang et al, 2006;Chen et al, 2018), several NPF events were also observed onboard the G-1 during the HI-SCALE campaign. These newly formed particles and their subsequent growth may be a significant contributor to CCN.…”
Section: New Particle Formationsupporting
confidence: 86%
“…Similar to previous studies at the SGP (Marinescu et al, 2019;Wang et al, 2006;Chen et al, 2018), several NPF events were also observed onboard the G-1 during the HI-SCALE campaign. These newly formed particles and their subsequent growth may be a significant contributor to CCN.…”
Section: New Particle Formationsupporting
confidence: 86%
“…If there is a significant concentration of particles with dry diameters above 470 nm, then D crit in Equation 3 will be artificially decreased, leading to an overestimation of the true value of κ. However the SGP site generally has very low concentrations of particles with dry size above ≈500 nm (Marinescu et al, 2019), and so we expect that large dry particles not captured by the SMPS will not significantly alter the supersaturation values presented here.…”
Section: Resultsmentioning
confidence: 86%
“…For example, Quan et al (2011) found average N a of 24,000 cm −3 in the North China Plain, and Mazoyer et al (2019) found that N a varied between 2000 and 20,000 cm −3 prior to fog events at the SIRTA site near Paris, with the variation mainly depending on the prevailing wind direction. Aerosol loading and variation in the aerosol size distribution at the SGP site were investigated by Marinescu et al (2019), who found a diurnal cycle in accumulation mode aerosols, with the highest concentrations occurring at night and being driven by nocturnal increases in nitrate and organic aerosol mass concentrations. The SGP site is rural and the surrounding area is primarily grassland and rangeland, so the lower N a may reflect the reduced anthropogenic influence at this site compared to the sites used in previous studies; this is also supported by the relatively high κ values shown in Table 3 (as compared to values previously reported from suburban and urban areas).…”
Section: Resultsmentioning
confidence: 99%
“…We then fit a two-mode lognormal distribution to these CCN-derived values of aerosol concentration as a function of size. This method can be considered a simplified form of that explored in Marinescu et al (2019); our intent here is to capture the first-order temporal variability of the aerosol-capturing the firstorder spatial variability will follow. To this end, we set the shape of the size distribution equal to the best-fit interpolation from the CCN measurements made in the morning for that day, and allowed the total concentration to vary over each day according to the total CN count.…”
Section: Modeling Case Selection and Aerosol Inputsmentioning
confidence: 99%